1996
DOI: 10.1104/pp.110.4.1239
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Isolated Chloroplasts Contain an Integrated Lipid-Synthesizing Assembly That Channels Acetate into Long-Chain Fatty Acids

Abstract: High rates of light-dependent fatty acid synthesis from acetate were measured in isolated chloroplasts that were permeabilized to varying extents by resuspension in hypotonic reaction medium. The reactions in hypotonic medium unsupplemented with cofactors were linear with time and were directly proportional to chlorophyll concentration, suggesting that the enzymes and cofactors of fatty acid synthesis remained tightly integrated and thylakoid associated within disrupted chloroplasts. Permeabilized chloroplasts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 40 publications
1
46
0
Order By: Relevance
“…In microarray analysis of leaves, flowers, and roots, two plastidial ACP genes were found to be expressed at a similar level compared with stearoyl-ACP desaturase. This observation of a similar concentration of substrates and enzymes is consistent with recent suggestions of channeling of acyl-ACP intermediates in the plastidial FAS machinery (Roughan and Ohlrogge, 1996).…”
Section: De Novo Fatty Acid Biosynthetic Enzymes and Acyl-acpsupporting
confidence: 79%
See 1 more Smart Citation
“…In microarray analysis of leaves, flowers, and roots, two plastidial ACP genes were found to be expressed at a similar level compared with stearoyl-ACP desaturase. This observation of a similar concentration of substrates and enzymes is consistent with recent suggestions of channeling of acyl-ACP intermediates in the plastidial FAS machinery (Roughan and Ohlrogge, 1996).…”
Section: De Novo Fatty Acid Biosynthetic Enzymes and Acyl-acpsupporting
confidence: 79%
“…Although easily dissociable in vitro, it has been suggested that these enzymes are associated in vivo in some more organized form (Roughan and Ohlrogge, 1996). However, almost no information is available regarding the stoichiometric ratios of the component enzymes.…”
Section: De Novo Fatty Acid Biosynthetic Enzymes and Acyl-acpmentioning
confidence: 99%
“…There are some indications that the plastidic enzymes involved in fatty acid biosynthesis are part of a complex (Roughan and Ohlrogge, 1996). It is also likely that MKS1 is part of this protein complex in the L. hirsutum glands and that its kinetic parameters are quite different when it acts as part of such a complex.…”
Section: The Mechanism Of Action Of Mks1mentioning
confidence: 99%
“…5), these effects occur in the range of 0.1 to 1 mM, below the range of the stromal concentrations of these effectors (1-3 mM). However, recent findings indicate that the chloroplastic ACCase along with acetyl-COA synthetase and the fatty acid synthase enzymes may be in a multienzyme complex (Roughan and Ohlrogge, 1996). This complex appears to sequester and recycle a small pool of ATP/ADP nucleotides it requires for catalysis.…”
Section: Biochemical Characterization Of Biotin Carboxylasementioning
confidence: 99%